KONSEP IDEAL DALAM MEWUJUDKAN PRINSIP PENYELESAIAN SENGKETA PENGGUNA FINTECH LENDING BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR77/POJK.01/2016 - Annisa Fidela Shanti; ' Pranoto; Kukuh Tedjomurti (Jurnal Privat Law, 2023)
AbstractThis article aims to find out the ideal concept to realize the principle of user dispute resolution in accordance with the Financial Services Authority Regulation No. 77/POJK.01/2016. The research method used is normative legal research. Sources of legal materials used are primary legal materials and secondary legal materials, with legal material analysis techniques using the syllogism method and interpretation using deductive thinking patterns. Based on the results of research conducted by the author, it is known that there are several ways of resolving disputes intransactions  Fintech  Lending,  but  the Financial  Services Authority whose function is to organize an integrated regulation and supervision system for all activities in the financial services sector has not yet formed an Alternative Dispute Resolution Institution in the field of Fintech Lending. Financial Services Authority Regulation Number 77/POJK.01/2016 is also considered not effective in resolving disputes in technologybased money lending and borrowing transactions. The Financial Services Authority Regulation Number 77/POJK.01 /2016 Is considered not effective because in Article 29 letter e only explains that the settlement of user disputes is simple, fast, and affordable, there is no clear mechanism related to the settlement of the user dispute Fintech Lending, So that the Organizers Fintech Lending do not yet have guidelines for resolving disputes that result in the Operator Fintech Lending being initials of theable to elect the Registrar’s Office Of the South Jakarta District Court To settle disputes with users, especially  Lenders. The  importance Of the  Financial  Services Authority  to establish  an Alternative Dispute Resolution Institution In the field of Fintech Lending So that  Users ofservices Fintech Lending especially  the Lender Get clarityKeywords: Fintech Lending; Ideal Concept; Dispute resolution AbstrakArtikel ini bertujuan untuk  mengetahui konsep  yang  ideal untuk  mewujudkan prinsip penyelesaian sengketa pengguna sesuai dengan Peraturan Otoritas Jasa Keuangan Nomor 77/POJK.01/2016. Metode penelitian yang digunakan adalah penelitian hukum normatif. Sumber bahan hukum yang digunakan adalah bahan hukum primer dan bahan hukum sekunder, dengan teknik analisis bahan hukum menggunakan metode silogisme dan interpretasi dengan menggunakan pola berpikir deduktif. Berdasarkan hasil penelitian yang penulis lakukan, diketahui bahwa terdapat beberapa cara menyelesaikan sengketa dalam transaksi Fintech Lending, namun Otoritas Jasa Keuangan yang berfungsi untuk menyelenggarakan sistem pengaturan dan pengawasan terintegrasi terhadap keseluruhan kegiatan di dalam sektor jasa keuangan belum membentuk Lembaga Alternatif Penyelesaian Sengketa  dalam  bidang  Fintech  Lending.  Peraturan  Otoritas  Jasa  Keuangan Nomor   77/POJK.01/2016   juga   dinilai   belum   efektif  untuk   menyelesaikan sengketa dalam transaksi pinjam meminjam uang berbasis teknologi. Peraturan Otoritas Jasa Keuangan Nomor 77/POJK.01/2016 tersebut dinilai belum efektif karena dalam Pasal 29 huruf e hanya menjelaskan bahwa penyelesaian sengketa pengguna secara sederhana, cepat, dan biaya terjangkau, tidak ada mekanisme yang jelas terkait penyelesaian sengketa pengguna Fintech Lending tersebut, sehingga para Penyelenggara Fintech Lending belum memiliki pedoman untuk menyelesaikan sengketa yang mengakibatkan Penyelenggara Fintech Lending berinisial dapat memilih Kantor Kepaniteraan Pengadilan Negeri Jakarta Selatan untuk menyelesaikan sengketa dengan pengguna khususnya Lender. Pentingnya Otoritas Jasa Keuangan untuk membentuk Lembaga Alternatif Penyelesaian Sengketa dalam bidang Fintech Lending tersebut  agar para Pengguna layanan Fintech Lending khususnya Lender tersebut mendapatkan kejelasanKata Kunci: Fintech Lending; Konsep Ideal; Penyelesaian Sengketa